Three-Dimensional Extension Of Kirkpatricks Planar Point Location Method. - Talib, Abdullah Zawawi; Md Ismail, Ahmad Izani (2005)
The point location problem is an important problem in computational geometry. Most of the methods that have been developed have been for the planar point location problem.